Poor adherence to medication as assessed by the Morisky Medication Adherence Scale‐8 and low satisfaction with treatment in 237 psoriasis patients. Issue 4 (27th February 2015) - Saeki, Hidehisa; Imafuku, Shinichi; Abe, Masatoshi; Shintani, Yoichi; Onozuka, Daisuke; Hagihara, Akihito; Katoh, Norito; Murota, Hiroyuki; Takeuchi, Satoshi; Sugaya, Makoto; Tanioka, Miki; Kaneko, Sakae; et al.
Abstract Previously we assessed the medication adherence for oral and topical remedies by a translated Japanese version of the Morisky Medication Adherence Scale‐8 (MMAS‐8) together with socioeconomic backgrounds in 3096 Japanese dermatological patients, and found the medication adherence, especially to topical drugs, was poor in these patients. In order to elucidate the disease‐specific sociomedical factors, we further sub‐analyzed the medication adherence in 237 psoriasis patients and compared it with that in other dermatological diseases such as atopic dermatitis, urticaria or tinea. This study was conducted among patients registered in monitoring system and 3096 eligible patients were enrolled. Our web‐based questionnaire included the following items such as age, sex, annual income, main health‐care institution, experience of effectiveness by oral or topical medication, overall satisfaction with treatment, and MMAS‐8 for oral or topical medication. Mean adherence score by MMAS‐8 was 5.2 for oral and 4.3 for topical medication. More patients with psoriasis used a university hospital and fewer used a private clinic compared with those with the other skin disease patients. Experience of drug effectiveness by oral medication and overall satisfaction with treatment was lower in psoriasis patients than in other patients. In oral medication, significantly better adherence was observed in those of higher age and with higher annual income. The adherence to medication, especially to topical drugs, was poor in 237 psoriasis patients. We speculated that some severe psoriasis patients were not sufficiently treated systemically and were resistant to topical therapy, leading to poor adherence.